Cytotoxic Virulence Predicts Mortality in Nosocomial Pneumonia Due to Methicillin-Resistant Staphylococcus aureus - Rose, Hannah R. (J Infect Dis, 2015)
The current study identified bacterial factors that may improve management of methicillin-resistant Staphylococcus aureus (MRSA) nosocomial pneumonia. Isolates were obtained from 386 patients enrolled in a randomized, controlled study of antibiotic efficacy. Isolates were screened for production of virulence factors and for vancomycin susceptibility. After adjustment for host factors such as severity of illness and treatment modality, cytotoxic activity was strongly and inversely associated with mortality; however, it had no effect on clinical cure. Isolates having low cytotoxicity, which were derived largely from healthcare-associated clones, exhibited a greater prevalence of vancomycin heteroresistance, and they were recovered more often from patients who were older and frailer. Additionally, a clone with low cytotoxic activity was associated with death and poor clinical improvement. Clone specificity and attenuated virulence appear to be associated with outcome. To our knowledge, these are the first correlations between MRSA virulence and mortality in nosocomial pneumonia.